Disease-Associated SNPs in Inflammation-Related lncRNAs - Castellanos-Rubio, Ainara; Ghosh, Sankar (Frontiers in Immunology, 2019)
Immune-mediated diseases, such as celiac disease, type 1 diabetes or multiple sclerosis, are a clinically heterogeneous group of diseases that share many key genetic triggers. Although the pathogenic mechanisms responsible for the development of immune mediated disorders is not totally understood, high-throughput genomic studies, such as GWAS and Immunochip, performed in the past few years have provided intriguing hints about underlying mechanisms and pathways that lead to disease. More than a hundred gene variants associated with disease susceptibility have been identified through such studies, but the progress towards understanding the underlying mechanisms has been slow. The majority of the identified risk variants are located in noncoding regions of the genome making it difficult to assign a molecular function to the SNPs. However, recent studies have revealed that many of the noncoding regions bearing disease-associated SNPs generate long noncoding RNAs (lncRNAs). LncRNAs have been implicated in several inflammatory diseases, and many of them have been shown to function as regulators of gene expression. Many of the disease associated SNPs located in lncRNAs modify their secondary structure, or influence expression levels, thereby affecting their regulatory function, hence contributing to the development of disease.